Perspectives on strained intensive care unit capacity: A survey of critical care professionals. - Dawn Opgenorth; Henry T Stelfox; Elaine Gilfoyle; R T Noel Gibney; Michael Meier; Paul Boucher; David McKinlay; Christiane N Job McIntosh; Xiaoming Wang; David A Zygun; Sean M Bagshaw (PLoS ONE, 2018)
BACKGROUND:Strained intensive care unit (ICU) capacity represents a supply-demand mismatch in ICU care. Limited data have explored health care worker (HCW) perceptions of strain. METHODS:Cross-sectional survey of HCW across 16 Alberta ICUs. A web-based questionnaire captured data on demographics, strain definition, and sources, impact and strategies for management. RESULTS:658 HCW responded (33%; 95%CI, 32-36%), of which 452 were nurses (69%), 128 allied health (19%), 45 physicians (7%) and 33 administrators (5%). Participants (agreed/strongly agreed: 94%) reported that strain was best defined as "a time-varying imbalance between the supply of available beds, staff and/or resources and the demand to provide high-quality care for patients who may become or who are critically ill"; while some recommended defining "high-quality care", integrating "safety", and families in the definition. Participants reported significant contributors to strain were: "inability to discharge ICU patients due to lack of available ward beds" (97%); "increases in the volume" (89%); and "acuity and complexity of patients requiring ICU support" (88%). Strain was perceived to "increase stress levels in health care providers" (98%); and "burnout in health care providers" (96%). The highest ranked strategies were: "have more consistent and better goals-of-care conversations with patients/families outside of ICU" (95%); and "increase non-acute care beds" (92%). INTERPRETATION:Strain is perceived as common. HCW believe precipitants represent a mix of patient-related and operational factors. Strain is thought to have negative implications for quality of care, HCW well-being and workplace environment. Most indicated strategies "outside" of ICU settings were priorities for managing strain.